Suluk Ritual and Mental Health: Exploration of the Experiences of the Suluk of the Tarekat Naqshbandiyah Khalidiyah Babussalam (TNKB), Indonesia - Muzakkir; Amroeni Darajat (Universitas Islam Negeri Palopo, 2026)
This study aimed to examine the relationship between suluk rituals and mental health. To achieve this objective, questions were formulated about the nature of suluk rituals and ethical considerations to determine its relationship with mental health. Qualitative data was selected using a case study approach to answer the formulated questions. The main data sources in this study are murshid, caliphs, and congregations. Data were collected using observation, interviews, and documentation, and analyzed in different stages with the presentation of results. The result showed that the suluk rituals is are a form of spiritual training activity requiring each congregations to carry out a series of rituals, such as dhikr, muraqabah, tawajuh, and others. To discipline the congregations in its implementation, ethical guidelines are established, requiring adherence and implementation before, during the process, and at the end of the process. These ethical guidelines consistently maintain the practices during the suluk. Furthermore, the suluk rituals with mental health was found through the intersubjective experiences of the pilgrims who perform the rituals through recognition of the changes experienced, namely becoming calm and able to think rationally. The practice of dhikr, which is the main activity of the suluk rituals, has significantly contributed to shaping the mental health of the congregations. Consequently, it can be confirmed that the suluk rituals positively influenced mental health formation.